Bleomycin Polidocanol Foam (BPF) Stability – In Vitro Evidence for the Effectiveness of a Novel Sclerosant for Venous Malformations. (June 2020) - Sun, Yi; Gu, Hao; Yang, Xi; Cai, Ren; Shang, Ying; Hu, Li; Wang, Yungying; Chen, Hui; Lin, Xiaoxi
Abstract : Objective: This study investigated the in vitro stability of a novel sclerosant, bleomycin polidocanol foam (BPF), for venous malformation (VM) sclerotherapy. Methods: The study was designed with control groups treated with polidocanol (0.5%, 1%, and 3%) only. The experimental groups included 21 BPFs, which was made by dissolving bleomycin at seven different concentrations (0.1%–1.5%) in polidocanol (0.5%, 1%, and 3%). The Tessari method was used to prepare sclerosant foam with a liquid:gas ratio of 1:4 at room temperature in vitro . The foam stability was measured for each group. The decay process, one component of foam stability, was recorded with a camera. Foam decay process experiments were performed 10 times per group. The stability indices included drainage rate, drainage time, half life, and microscopic measurement of the foams (mean bubble diameter, minimum and maximum bubble diameters, wall thickness, and bubble diameter distribution). Results: Compared with the control groups, the half lives of BPFs mainly increased significantly with the addition of bleomycin ( p  < .001). BPF with 3% polidocanol and 0.1% bleomycin recorded the highest half life (246 ± 1.6 sec), and this group also achieved the smallest bubble diameter and wall thickness (69.9 μm and 5.80 μm) among the experimental groups. For the same polidocanol concentration, the bubble diameter and wall thickness increased when bleomycin was added. Conclusion: Bleomycin concentrations account for different BPF stability. BPF stability mainly increased significantly with the addition of a small amount of bleomycin but this advantage was no longer apparent with increasing bleomycin dose.